Influence of Maternal Education on Child Health Status in Karachi,Pakistan - Faryal Nawab; Kiran Fatima; Tehreem malik; Anum Mengal; Banadi Haji Syed; Alina Atif (Annals of Abbasi Shaheed Hospital and Karachi Medical & Dental College, 2025)
Objective: To explore the influence of maternal education on childhood under-nutrition, timely vaccination, breastfeeding, and weaning practices among children under 5 years of age, Sindh, Pakistan. Methods: A community-based cross-sectional study was conducted for six months, from June 2022 to December 2022, at Burmi Sharif, Korangi Karachi. About 1691, mothers between the ages of 15-49, who had at least one living child in the past five years, were included through a non-probability purposive sampling technique. The study was approved by the Ethical Review Committee of Sohail University. The education of these mothers was an independent variable while the dependent variables were child mortality, immunization, nutrition status, breastfeeding, and weaning practices. SPSS version 27 was used to analyze the data. Logistic regression analysis was performed. A P-value of less than 0.5 was considered significant. Results: The mean age of children was 2.82 ± 1.8 SD. About 96% of children were found to be vaccinated. Children of educated mothers had 1.8 times higher odds of being fully vaccinated (p= 0.058), 1.3 odds of starting weaning at 6 months of age (p=0.033), 30 times higher odds to be not stunted (p=0.001) and 1.2 times higher odds of immediate initiation of breastfeeding (p=0.003). Conclusion: The present study highlights the importance of maternal education on a child’s health since children of educated mothers had far better health outcomes than those who were not educated. Therefore, maternal education is considered one of the most important factors in a child’s health.